Dualisme Pengaturan Mengenai Pemberhentian Pegawai Negeri Sipil - Maria Arbina (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
The enactment of Law Number 5 Year 2014 on State Civil Apparatus and Government Regulation Number 11 of 2017 concerning Civil Servants Management raises a dualism of regulation regarding dismissal of civil servants. Because in addition to the two regulations, Government Regulation Number 53 of 2010 concerning Discipline of Civil Servants still applies. This raises a polemic, whether civil servants involved in corruption are subject to penalties based on Government Regulation Number 53 of 2010 concerning Discipline of Civil Servants or Government Regulation Number 11 of 2017 concerning Management of Civil Servants. Responding to the polemic, the Constitutional Court's decision No. 87 / PUU-XVI / 2018 concerning the Testing of Law Number 5 of 2014 concerning the State Civil Apparatus which in its consideration stated that Civil Servants were convicted of committing criminal offenses or related criminal acts with a position subject to a termination not respectfully in accordance with Government Regulation Number 11 of 2017 concerning Management of Civil Servants.